Synergism between cruising cod and ambush sculpin predators on 0-group gadoids is modified by daylight cycle and presence of aggressive wolffish - Strand, Hans Kristian; Pedersen, Torstein; Christie, Hartvig C; Moy, Frithjof Emil (Journal of Experimental Marine Biology and Ecology, 2020)
Shorthorn sculpin ( Myoxocephalus scorpius ) and large cod (300–400 g body weight) are important predators on newly settled 0-group cod ( Gadus morhua ) and saithe ( Pollachius virens ) in Porsangerfjorden in northern Norway. The Atlantic wolffish ( Anarhichas lupus ) used to be abundant but is now very rare in the fjord. Video recorded experiments showed that interactions between shorthorn sculpins, wolffish and large cod affected predation rates on small 0-group cod and saithe in tanks with a gravel, cobble and seaweed ( Fucus serratus ) substrate. We found that sculpins were unable to catch 0-group specimens when they were the only predatory species in the experimental tank and the lights were left on 24 h a day (to simulate the midnight sun), and that they did not even attempt to catch them. The addition of a large cod to the tank increased sculpin attack rates and predation success significantly. The “cod effect” was due to 0-group specimens avoiding attacks by escaping into the cobbles or vegetation, were they could be more easily reached by the sculpins. When tanks were supplemented with a wolffish in addition to the cod, both sculpin and cod predation success was lowered by approximately 50% in the 24-h light regime. When the experimental setup was changed to a day/night light cycle, however, the wolffish presence had no effect. Also, sculpins in tanks without cod and wolffish went from consuming zero to 29% of the 0-group specimens in the tank when the light regime went from 24-h light to day/night. Sculpins and cod were most effective predators on 0-group cod and saithe at dusk/night/dawn, and the presence of a cruising predator like cod increased sculpin predation success and probably vice versa . The experimental data indicate that rebuilding wolffish stocks in the fjord system may make the bottom substrate more protective for 0-group specimens of cod and saithe, by limiting the foraging volume of an effective bottom-dwelling 0-group predator like the sculpin. Further field and lab studies must be ...